2022
DOI: 10.2196/40242
|View full text |Cite
|
Sign up to set email alerts
|

Chatbot-Delivered Cognitive Behavioral Therapy in Adolescents With Depression and Anxiety During the COVID-19 Pandemic: Feasibility and Acceptability Study

Abstract: Background Symptoms of depression and anxiety, suicidal ideation, and self-harm have escalated among adolescents to crisis levels during the COVID-19 pandemic. As a result, primary care providers (PCPs) are often called on to provide first-line care for these youth. Digital health interventions can extend mental health specialty care, but few are evidence based. We evaluated the feasibility of delivering an evidence-based mobile health (mHealth) app with an embedded conversational agent to deliver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 58 publications
0
52
0
Order By: Relevance
“…Of the 25 studies, 19 were recently published (between 2020 and 2023) 8 10 , 12 , 26 40 . Studies were conducted predominantly in the US ( n = 12) 11 , 12 , 27 , 28 , 33 , 34 , 38 , 41 45 , followed by Europe ( n = 5) 10 , 26 , 29 , 32 , 35 , Asia ( n = 4) 9 , 31 , 36 , 39 , New Zealand ( n = 2) 37 , 40 , and Australia ( n = 1) 30 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 25 studies, 19 were recently published (between 2020 and 2023) 8 10 , 12 , 26 40 . Studies were conducted predominantly in the US ( n = 12) 11 , 12 , 27 , 28 , 33 , 34 , 38 , 41 45 , followed by Europe ( n = 5) 10 , 26 , 29 , 32 , 35 , Asia ( n = 4) 9 , 31 , 36 , 39 , New Zealand ( n = 2) 37 , 40 , and Australia ( n = 1) 30 .…”
Section: Resultsmentioning
confidence: 99%
“…In total, there were 21 different agents described in the included studies. Only 3 of the CA were the focus of more than one study – Paro 11 , 41 , 45 , Nao 8 , 38 , and Woebot 12 , 42 . These automated CAs were predominantly disembodied chatbots ( n = 15) 10 , 26 , 28 32 , 35 37 , 40 , 42 44 , followed by robots ( n = 7) 8 , 9 , 33 , 34 , 38 , 41 , 45 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic alliance, a construct familiar in psychotherapeutic treatment outcomes research, refers to the therapeutic relationship and affective bond between provider and patient and is associated with the efficacy of psychotherapy [26,27]. A randomized controlled pilot among adolescents aged 13-17 years (n=17) demonstrated W-GenZD's preliminary feasibility and utility in an outpatient primary care pediatric setting [28], but further evaluation of its feasibility and acceptability as well as clinical efficacy is warranted.…”
Section: Technology-leveraged Mh Care Interventionsmentioning
confidence: 99%
“…A 12 weeks randomized controlled trial during the pandemic evaluated the feasibility and efficacy of using a natural language and machine learning chat-based app (W-GenZ) for mood tracking and for facilitating tailored intervention in 13 to 17 years-olds with moderate symptoms of depression (58). The outcome of the study revealed that use of the app was feasible and acceptable to both the teenagers and their parents, and depressive symptoms in the young participants showed a shift from the moderate to mild category by 4 weeks in the treatment arm compared to the control group, as determined using Patient Health Questionnaire (PHQ-9) scores.…”
Section: Chat-and Psychoeducation-based Appsmentioning
confidence: 99%